The Lived Experiences of Nurses Working During the COVID-19 Pandemic. Issue 3 (May 2021) - Robinson, Ruthie; Stinson, Cynthia Kellam
Abstract : Background: Previous research on nurses during pandemics has focused on nurses working in one facility or type of unit; this study focuses on nurses caring for COVID-19 patients in a variety of units in different sites across the United States. Objective: The aim of this study was to understand the experiences of registered nurses working with hospitalized COVID-19 patients. Methods: This study used a hermeneutic phenomenology design. Semistructured interviews via telephone were conducted and then transcribed verbatim. Colaizzi's method of analysis was used. Data saturation was achieved with 14 participants. Results: Three major themes were evident. They were "the human connection, " "the nursing burden, " and "coping." Subthemes were identified under each major theme. Discussion: This study depicted nurses who are caring, empathetic, and resilient. They had many recommendations for fellow nurses, the public, and health care organizations.